Dança clássica indiana: segundo os mestres, as escrituras e os praticantes - Karen Cristine Veloso Martins (2017)
The debate around what is defined as the Indian classical dance is the theme of this research. The proposal of this research is to expose that debate in its many aspects and developments. For that matter, the literature review was used along with the personal experience as a bharatanyam dancer a style of Indian classical dance -, as a trained spectator in the theoretical studies of that art, as well as the experience as an apprentice of bharatanyam in Brazil, Índia, and United States, and as a teacher in Brazil. Such experiences, and the confrontation between the Indian art theory and its practice, raised the issues regarding the existence of fundamental and fixed elements that define the Indian classical dance, nya, in contrast with those which are flexible, and go through transformations according to time, to the place where the dance is practiced, and to the circumstances in which it is executed. The development of the research has shown the complexity of the subject, which goes beyond the simple assertion that the classical dances of India has its origins in the scripture called nya stra. Such complexity is revealed in the following facts: 1) folk dances or non-classical dances also find their origin in that scripture, so this cannot be considered an absolut or the only parameter; 2) apparently, some essential points found in the scripture are not found in the dance; 3) the tradition is a living element, and therefore, it is changeable, while the writing is frozen in time even though de readers view might provide new analysis ; 4) the practitioners themselves, and the researchers, disagree on several points concerning the definition of the classical dance in India. With the increasing globalization and intercultural relations, along with the thirst for novelty and the increasingly rapid changes in the world, many dancers and researchers believe that it is necessary to establish the limits and the parameters of the Indian classical dance, without immobilizing it, however, in an attempt to facilitate its survival within the current context and in the future, especially when some state that much of it seems to have been already lost in the past. Thus, the research seeks to cooperate providing a reflection regarding the fundamentals that could be maintained, so that the dance will not descaracterize nor will perish, but which will also give room for the flexibility needed so that it can remain alive and relevant.